2018
DOI: 10.29082/ijnms/2018/vol2.iss02.94
|View full text |Cite
|
Sign up to set email alerts
|

Challenge in Social Support for Improving Quality of Life People With Hiv/Aids

Abstract: Background Became HIV-positive people was heavy burden in life, where complex issues  always dealt. The complexity of the problem might be faced certainly could impact on the quality of life. One factor that had important role in the quality of life was social support. Objective The aim of this research was to know the correlation between social support and quality of life people with HIV/AIDS, Methods the research design was used correlation analytic with cross sectional approach. The population f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results of the research conducted by (5) showed that among people who get social support, 46.7% do not blame themselves and express what they feel. While the results of research conducted by (Roifah, Akbar, & Sudarsih, 2018)show that through social support, a person feels valued and loved, does not feel alone in dealing with all problems, and feels part of the scope of the family and the surrounding environment. Lack of social support can impact people with HIV/AIDS, including their physical and psychological health.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the research conducted by (5) showed that among people who get social support, 46.7% do not blame themselves and express what they feel. While the results of research conducted by (Roifah, Akbar, & Sudarsih, 2018)show that through social support, a person feels valued and loved, does not feel alone in dealing with all problems, and feels part of the scope of the family and the surrounding environment. Lack of social support can impact people with HIV/AIDS, including their physical and psychological health.…”
Section: Introductionmentioning
confidence: 99%